Editors' Choice—In Situ Electrochemical Evaluation of Post-CMP Cleaning Reactions for Cobalt and Copper Films under Brushing Conditions. (1st January 2019) - Johnson, C. A.; Roy, D.
Abstract : The sub-10 nm technology node has introduced significant chemical complexities in the associated processing steps of chemical mechanical planarization (CMP), and this has correspondingly convoluted the post-CMP cleaning (PCMPC) protocols. Focusing on selected cleaning chemistries, the present work demonstrates an in-situ tribo-electrochemical approach to developing fundamental knowledge of the PCMPC mechanisms for such systems. As model samples, the experiments use cobalt and copper thin films, deposited on wafer coupons, and treated in an alkaline CMP solution of acetate, H2 O2 and benzotriazole. These samples are subsequently studied in an alkaline PCMPC solution of oxalic acid, designed for cleaning both Co and Cu. The surface cleaning characteristics of the metals are assessed by tribo-electrochemical measurements in the presence of mechanical brushing with a commercial rotary brush for PCMPC. The tribo-electrochemical parameters of the PCMPC-active brushed wafer regions are extracted from the recorded data to determine the cleaning mechanisms. Open circuit potential and voltammetric measurements indicate that oxalate ions serve to remove the CMP residues, Co(OH)2 and Cu-oxides from Co and Cu surfaces, respectively, in the forms of oxalate complexes. The residue removal efficiencies, measured by ex-situ impedance spectroscopy, are found in the 85–89% range for both Co and C